Analisis Perubahan Penggunaan Lahan untuk Permukiman di Kecamatan Lubuak Alung Kabupaten Padang Pariaman 2011 dan 2023 - Jumaidi, Rabby; Prarikeslan, Widya (Lembaga Yasin AlSys, 2024)
The purpose of this study was to determine 1) How the extent of land use change for settlement in Lubuk Alung sub-district in 2011 and 2023, 2) How is the relationship between land use change for settlements with the RTRW of Padang Pariaman Regency. The type of research in this study is Quantitative and uses Data used in the study in the form of secondary data, namely Landsat 7 images with a period of 2011 & Landsat 8 with a period of 2023, shapefile RTRW Padang Pariaman Regency Year 2010 -2030. The analysis method used is Overlay which is used to determine land use changes and the alignment of the Lubuk Alung District spatial plan data with the existing land use of rice fields and settlements. Forest area decreased by 12.28%, while mixed gardens, shrubs, and settlements increased by 22.31%, 79.80%, and 127.68% respectively. However, paddy fields decreased by 21.45%. Furthermore, this research relates land use change for settlements in Lubuk Alung to the Regional Spatial Plan (RTRW) of Padang Pariaman Regency. The RTRW spatial pattern data is the basis for spatial planning. Although there has been an increase in the area of settlement land that is in accordance with the spatial pattern from 195 ha in 2011 to 330 ha in 2023, there is still a portion that is not in accordance, reaching 609 ha in 2023. This indicates a mismatch between land use and the spatial plan.